An Analisis Epistemological Obstacle Berdasarkan Kesalahan Menyelesaikan Soal Matematika Materi Segitiga Siswa Kelas VII SMP Negeri 3 Mataram Tahun Ajaran 2022/2023 - Ainun, Yusri; Sridana, Nyoman; Kurniati, Nani; Sarjana, Ketut (FKIP Universitas Mataram, 2024)
This research aims to describe epistemological obstacles based on errors in solving mathematics problems related to triangle material for class VII students at SMP Negeri 3 Mataram. This research method uses a qualitative descriptive method with data collection methods including diagnostic tests and questionnaires. The sample was selected from class VII-4 of SMP Negeri 3 Mataram where the sample search method was carried out using tests. Determination of the sample using a purposive sampling technique. The sample selected was six students based on the results of tests and grouped into three groups with each group consisting of 2 students in the high, medium, and low error category and then given a questionnaire. The results of the research show that the types of epistemological obstacles experienced by students are conceptual epistemological obstacles with a percentage of 56.99%, procedural epistemological obstacles with a percentage of 95.70%, and operational technique epistemological obstacles with a percentage of 79.57%. For students with a high error category, the percentage of conceptual epistemological obstacles is 100%, procedural epistemological obstacles are 100%, and operational technique epistemological obstacles are 100%. Meanwhile, for students with the moderate error category, the percentage of conceptual epistemological obstacles was 66.67%, procedural epistemological obstacles were 100%, and operational technique epistemological obstacles were 89.86%. Finally, for students in the low error category, the percentage of conceptual epistemological obstacles was 5.56%, procedural epistemological obstacles were 72.22%, and operational technique epistemological obstacles were 33.33%.